Development of the Attitude Scale for Wasteful Behaviors Towards Nurses and Examination of Its Psychometric Properties - Ülkü Baykal; Seda Tuğba Baykara Mat (Journal of Nursology)
Objective: This study aims to develop the "Nurses’ Wasteful Behaviors Attitude Scale" as a new measurement tool to evaluate the attitudes of nurses’ wasteful behaviors.Methods: In the final phase of this three-phase study, a comprehensive literature review was conducted to create a new item pool of 52 items to minimize potential biases in the scale items and to communicate effectively with nursing professionals. Following the content validity results, a 50-item scale draft was obtained. Data were obtained online from 500 nurses between February and September 2023.Results: The content validity index of the scale stands at 0.96. Following the exploratory factor analysis, it was determined that the scale comprises 30 items distributed across five sub-dimensions, which collectively account for 58.17% of the total variance. Moreover, the Cronbach's alpha coefficient yielded a value of .93.Conclusion: The scale has high internal consistency, time invariance, and high fit indices. This scale can help take initiatives to prevent wasteful behaviors in the hospitals and ensure sustainability.